Curcumin/piperine modulates the butyrate levels and alleviates diabetic kidney disease via Nrf2/HO-1 signaling pathway - Yinan Zhu; Lina Sun; Zhaoan Guo; Peiqing Xin; Feng Huang; Lei Song; Yulin Man; Miaomiao Ren; Zhongwei Ma; Ying Wang (Renal Failure)
Objectives This study investigates whether curcumin/piperine (C/P) modulates butyrate levels and mitigates diabetic kidney disease (DKD) via the nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling pathway.Methods Eight-week-old mice were treated with C/P for 12 weeks, fecal samples were analyzed for short-chain fatty acids, and inflammatory markers in blood and kidneys were measured. Pathological staining and microscopy assessed the kidney and intestinal tissue morphology. Immunohistochemical detection of the expression of inflammatory markers in the kidneys and intestines. In vitro, the human proximal renal tubular cell line (HK-2) cells were exposed to high glucose (HG) and pretreated with C/P and sodium butyrate (NaB) to observe changes in inflammatory and oxidative stress markers. ML385 helped assess the role of the Nrf2/HO-1 pathway in the effects of C/P and NaB on inflammation and oxidative stress in DKD.Results Curcumin/piperine significantly improved renal injury and intestinal structural integrity, upregulated the expression of macrophage antigen CD68 and other inflammatory markers in the kidneys, and increased NaB levels in feces (p < .05). High glucose conditions enhanced inflammation and oxidative stress in HK-2 cells, whereas C/P and NaB pretreatment significantly inhibited these effects, reducing interleukin-6, IL-1β and other markers (p < .05), and increasing Nrf2 and HO-1 expression. Nrf2 inhibitor ML385 reduces the expression of Nrf2 and HO-1, and weakens the beneficial effects of C/P and NaB on HK-2 cells.Conclusions Curcumin/piperine enhances renal and intestinal integrity and modulates NaB levels to alleviate DKD through the Nrf2/HO-1 signaling pathway.